РЕЗУЛЬТАТИ ПЕДАГОГІЧНОГО ЕКСПЕРИМЕНТУ З ФОРМУВАННЯ ІНФОРМАЦІЙНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНЬОГО ПЕДАГОГА ПРОФЕСІЙНОГО НАВЧАННЯ В ЗАКЛАДАХ ВИЩОЇ ОСВІТИ (World Science, 2019)
Training teachers is an important task of modern pedagogy and requires new approaches to the organization of the educational process. The use of information and communication technologies for the purpose of forming the information competence of the future vocational teacher is an important element of the formation of his professional competence. The article describes the stages of conducting a pedagogical experiment to develop the information competence of a future teacher of vocational training in domestic higher education institutions. The organization and methodology of the experimental study are described in detail, its results are given, the methods of diagnostics are described and so on.